Comparative analysis of the microbiomes of strawberry wild species Fragaria nilgerrensis and cultivated variety Akihime using amplicon-based next-generation sequencing - Wang, Zongneng; Dai, Qingzhong; Su, Daifa; Zhang, Zhenrong; Tian, Yunxia; Tong, Jiangyun; Chen, Shanyan; Yan, Congwen; Yang, Junyu; Cui, Xiaolong (Frontiers in Microbiology, 2024)
Fragaria nilgerrensis is a wild strawberry species widely distributed in southwest China and has strong ecological adaptability. Akihime (F. × ananassa Duch. cv. Akihime) is one of the main cultivated strawberry varieties in China and is prone to infection with a variety of diseases. In this study, high-throughput sequencing was used to analyze and compare the soil and root microbiomes of F. nilgerrensis and Akihime. Results indicate that the wild species F. nilgerrensis showed higher microbial diversity in nonrhizosphere soil and rhizosphere soil and possessed a more complex microbial network structure compared with the cultivated variety Akihime. Genera such as Bradyrhizobium and Anaeromyxobacter, which are associated with nitrogen fixation and ammonification, and Conexibacter, which is associated with ecological toxicity resistance, exhibited higher relative abundances in the rhizosphere and nonrhizosphere soil samples of F. nilgerrensis compared with those of Akihime. Meanwhile, the ammonia-oxidizing archaea Candidatus Nitrososphaera and Candidatus Nitrocosmicus showed the opposite tendencies. We also found that the relative abundances of potential pathogenic genera and biocontrol bacteria in the Akihime samples were higher than those in the F. nilgerrensis samples. The relative abundances of Blastococcus, Nocardioides, Solirubrobacter, and Gemmatimonas, which are related to pesticide degradation, and genus Variovorax, which is associated with root growth regulation, were also significantly higher in the Akihime samples than in the F. nilgerrensis samples. Moreover, the root endophytic microbiomes of both strawberry species, especially the wild F. nilgerrensis, were mainly composed of potential biocontrol and beneficial bacteria, making them important sources for the isolation of these bacteria.This study is the first to compare the differences in nonrhizosphere and rhizosphere soils and root endogenous microorganisms between wild and cultivated strawberries. The findings have great value for the research of microbiomes, disease control, and germplasm innovation of strawberry.